Crisis Grammatical Use: Revealing Causes on EFL Students' Grammatical Erros - Siti Danti; Lala Nining Indrawati; Muawanah Muawanah; Khairul Wardani; Selamet Riadi Jaelani (Universitas Palan, 2023)
This study aimed to find out the causes on EFL Students' grammatical errors in speaking skills for students of English Language Department of Hamzanwadi University. This research employed descriptive qualitative research design. The participants of this study were 27 students from the second semester. The data were collected by three research instruments which were observation, interview, and documentation. The observation results showed that students often used their mother tongue for class interactions, rarely applying English during the learning. Moreover, the results of the interview showed that students faced challenges in applying grammar to speaking skills due to a lack of vocabulary, comprehension, writing-focused approach, and lack of practice. In conclusion, it is important to learn and practice grammar in speaking skill because fluency in grammar and language rules is crucial for students to become qualified teachers and avoid mistakes. Learning and practicing grammar in speaking skill is also essential for long-term capability.